Relationship of Soluble RAGE with Insulin Resistance and Beta Cell Function during Development of Type 2 Diabetes Mellitus - Subrata Kumar Biswas; Sabreena Mohtarin; Sonchita Rani Mudi; Taznuva Anwar; Laila Anjuman Banu; Sheikh Md. Khorshed Alam; Md. Fariduddin; M. Iqbal Arslan (Journal of Diabetes Research)
This study examined whether circulating levels of soluble receptor for advanced glycation end products (sRAGE) alter in prediabetes and correlate with insulin resistance (IR) and beta cell function in prediabetes and newly diagnosed type 2 diabetes mellitus (T2DM). Subjects without previous history of diabetes were recruited and grouped as control, prediabetes, and newly diagnosed T2DM. The control subjects (n=40) and people with prediabetes (n=52) and diabetes (n=66) were similar in terms of age, sex, BMI, systolic and diastolic BP, and fasting insulin level. HOMA-IR was found significantly higher in people with diabetes than control subjects (p<0.001) and people with prediabetes (p=0.005); and HOMA-%B was found significantly deteriorated in people with diabetes (p<0.001) compared to control subjects and people with prediabetes. However, serum sRAGE levels did not show any significant alteration in people with prediabetes compared to control subjects. Moreover, univariate and multivariate analyses did not identify any significant correlation and statistical association of sRAGE with HOMA-IR and HOMA-%B in people with prediabetes and newly diagnosed T2DM. Our data suggest that serum sRAGE levels do not alter in people with prediabetes compared to control subjects and do not correlate or associate with IR and beta cell function during development of T2DM.